Humeral torsion in the throwing arm of handball players - Pieper, H. G. (The American Journal of Sports Medicine, 1998)
Sport-specific upper extremity strain, mostly unilateral, during growth may lead to adaptations in soft tissue and bone. We investigated 51 male professional handball players between 18 and 39 years of age (average, 27 years), 39 right-handed and 12 left-handed. Thirty-eight players had no shoulder problems, and 13 had chronic shoulder pain. Humeral retrotorsion was determined by radiograph. The differences between the throwing and contralateral arms were compared with those of 37 controls who had no history of unilateral strain either through sports or profession. Standard statistical analysis was performed using the t-test. The retrotorsional angle of the humerus in the handball professionals' throwing arm was an average of 9.4 degrees larger in the dominant side than in the nondominant, with a side-to-side difference up to 29 degrees. In the control group, no statistically significant difference was found. In the group without chronic shoulder pain, the side-to-side difference was an average of 14.4 degrees more in the throwing arm than the other side. Players with chronic shoulder pain did not exhibit this increase, even showing an average decrease of humeral retrotorsion of 5.2 degrees in the throwing arm. The humeral retrotorsion increase can be explained as an adaptation to extensive external rotation in throwing practice during growth. Athletes who do not adapt this way seem to have more strain on their anterior capsules at less external rotation and develop chronic shoulder pain because of anterior instability.